Presence of Different Candida Species at Denture Wearers With Type 2 Diabetes and Clinically Healthy Oral Mucosa-Pilot Study - Petrović Sanja Matić; Barać Milena; Pfićer Jovana Kuzmanović; Radunović Milena; Jotić Aleksandra; Pucar Ana (Balkan Stomatological Society, 2018)
Background/Aim: The aim of this study was to examine prevalence of different Candida spp. at diabetics and nondiabetics wearing dentures without clinical signs of Denture Stomatitis (DS) and to study if some local and systematic factors are confounders for harboring Candida at these subjects. Material and Methods: Total of 60 subjects wearing partial or complete upper acrylic denture having at least half of palatal mucosa covered by denture were selected and stratified into three experimental groups: systematically health subjects; patients with diagnosed Type 2 Diabetes (T2D) and good glycoregulation; and T2D subjects with poorly regulated blood sugar level. Cotton swab samples were obtained from each patient from hard palate mucosa and denture surface. Swab cultures were made on Sabouraud dextrose agar and ChromAgar Media for distinciton of various Candida spp. Density growth was also measured. Results: Frequency of Candida spp. findings were similar between groups. At healthy subjects, only C.albicans was detected. At diabetics, C.albicans was the most common isolated species, followed by C.glabrata and C.tropicalis. Negative finding of yeasts on palatal mucosa, but positive on denture surface were detected at all groups, with the highest frequency (33.4%) at diabetics with poor glycoregulation. Denture surface was heavier colonized than hard palate mucosa. Duration of diabetes in years were only independent predictors for harboring Candida spp. at denture surface (Exp B=1.186, CI=1.047-1.344, p=0.007). Conclusions: Prosthesis of denture wearers without DS may serve as reservoir of Candida spp. Presence of more pathogenic and resistant non-albicans species are related to diabetics, even without clinical signs of DS.